Creation of Micro Market Structure in MSMEs in Review of Social Entrepreneurship Involvement, Government Policy and Empowerment - Prasetyo Harisandi; Ilham Muhammad Mardiputra; Zulfa Zakiyatul Hidayah; Steven Jordan Alvaro Ramba; Purwanto Purwanto (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
In order to better understand the role of social entrepreneurship, government policies, and empowerment initiatives, this study looks at how micromarket structure is created in micro, small, and medium-sized firms (MSMEs) in Indonesia. In order to conduct a survey with a stratified random sample of 215 Indonesian MSMEs, this study used a quantitative technique. Data analysis techniques included partial least squares structural equation modeling (PLS-SEM) and confirmatory factor analysis. The findings demonstrate the important influence of social entrepreneurship, governmental policies, and empowerment programs on the evolution of micro-market structures within the MSME sector. Social entrepreneurship in particular shows the potential of creative and socially conscious business ideas and has a positive effect on market structure. While empowerment programs like loan availability and training help to create a competitive market structure, government policies also have a significant impact on how the market is shaped. Policymakers, business owners, and development organizations that want to support effective and long-lasting market networks in Indonesia's MSMEs sector should take note of these findings.